Intravenous fosfomycin for pulmonary exacerbation of cystic fibrosis: Real life experience of a large adult CF centre. (June 2018) - Spoletini, G.; Kennedy, M.; Flint, L.; Graham, T.; Etherington, C.; Shaw, N.; Whitaker, P.; Denton, M.; Clifton, I.; Peckham, D.
Abstract: Background: The increased prevalence of multi-drug resistant strains of P.aeruginosa and allergic reactions among adult patients with cystic fibrosis (CF) limits the number of antibiotics available to treat pulmonary exacerbations. Fosfomycin, a unique broad spectrum bactericidal antibiotic, might offer an alternative therapeutic option in such cases. Aim: To describe the clinical efficacy, safety and tolerability of intravenous fosfomycin in combination with a second anti-pseudomonal antibiotic to treat pulmonary exacerbations in adult patients with CF. Method: A retrospective analysis of data captured prospectively, over a 2-years period, on the Unit electronic medical records for patients who received IV fosfomycin was performed. Baseline characteristics in the 12 months prior treatment, lung function, CRP, renal and liver function and electrolytes at start and end of treatment were retrieved. Results: 54 patients received 128 courses of IV fosfomycin in combination with a second antibiotic, resulting in improved FEV1 (0.94 L vs 1.24 L, p < 0.01) and reduced CRP (65 mg/L vs 19.3 mg/L, p < 0.01). Renal function pre- and post-treatment remained stable. 4% (n = 5) of courses were complicated with AKI at mid treatment, which resolved at the end of the course. Electrolyte supplementation was required in 18% of cases for potassium and magnesium and 7% for phosphate. Nausea was the most common side effect (48%), but was well controlled with anti-emetics. Conclusion: Antibiotic regimens including fosfomycin appear to be clinically effective and safe. Fosfomycin should, therefore, be considered as an add-on therapy in patients who failed to respond to initial treatment and with multiple drug allergies.